Analysis of Relay Protection for Offshore Wind Power Long-Distance Submarine Cable Transmission with High Resistance Station - Zhenlong TAN; Xiangyi QIAN; Wenchang CAI (Zhongguo dianli)
China’s current long-distance offshore wind power mainly follows a high-voltage AC transmission mode with an additional mid-range high-resistance compensation station. With regard to the problem about protection configuration for offshore wind power long-distance submarine cable transmission with the high resistance station, the relay protection configuration scheme and action logic are analyzed with a typical case. The reliability of range fault protection for submarine cables is studied, and then the impact of voltages at different measurement points taken by the offshore high resistance station on the calculation of capacitive current compensation is analyzed. In addition, the necessity of collecting the voltage on the offshore high-resistance side to calculate the differential compensation current is verified by simulation. The simulation results show that for the fault within the protection range, compared with collecting the actual voltage on the high-resistance side, taking the line-side voltage instead has a certain impact on the compensation current calculated by the protection device. To reduce the error in calculating the differential compensation current, the protection device should collect the voltage of the high-resistance station to calculate the differential compensation current and then work out the differential current after compensation to correct capacitive and reactive current.